2017
DOI: 10.2174/1871526517666161116104242
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Multidrug Resistant Mycobacterium tuberculosis Among New Cases in Al-Madinah Al-Monawarah, Saudi Arabia

Abstract: Background:The pattern of Mycobacterium tuberculosis susceptibility to first line drugs and multidrug resistance in Al-Madinah Al-Munawarah, a seasonally overcrowded are during Hajj and Omrah, is not well studied.Objective:This study aimed to investigate anti-tuberculosis drug resistance and its distribution among new cases in Al-Madinah Al-Monawarah.Methods:Study subjects included 622 patients with first time confirmed TB referred to the central tuberculosis laboratory in Al-Madinah between January 2012 and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
(38 reference statements)
5
8
0
Order By: Relevance
“…Age and sex differences among Saudi-and nonSaudi-TB patients were not statistically significant in this study. Similar findings were found in previous studies [13,14], in 622 Primary TB patients surveyed, in Madinah Al-Munawara in Saudi Arabia, a seasonal overcrowded area during Hajj and Umrah, either nationality or gender was not associated with MDRTB [13]. However, the frequency of non-Saudi was higher than that of Saudi [15], according to a previous report.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Age and sex differences among Saudi-and nonSaudi-TB patients were not statistically significant in this study. Similar findings were found in previous studies [13,14], in 622 Primary TB patients surveyed, in Madinah Al-Munawara in Saudi Arabia, a seasonal overcrowded area during Hajj and Umrah, either nationality or gender was not associated with MDRTB [13]. However, the frequency of non-Saudi was higher than that of Saudi [15], according to a previous report.…”
Section: Discussionsupporting
confidence: 90%
“…In the current report, the percentage of MDR-TB was 1.1 % with no substantial difference in any form of resistance to anti-tuberculosis drugs between Saudi and non-Saudi TB patients. These findings were consistent with Elhassan et al which found that MDR-TB was not associated with either nationality or gender [13]. This would lead to designating Saudi Arabia's health strategy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Prevalence in this study is similar to a recent study from Madinah Almunawarrah, where it was reported to be 4.0%. 9 However, a study from the Najran region of Saudi Arabia reported a very high prevalence (20.6%) of MDR TB. 10 A possible reason for this high prevalence as mentioned by the authors is that the Najran region is close to the border of Yemen, which has the highest TB burden in the region and there was frequent movement of people across the border.…”
Section: Discussionmentioning
confidence: 98%
“…Infection with TB is the leading cause of mortality among HIVinfected patients. According to World Health Organization, 25% of fatalities among people infected with HIV are due to the TB disease [7]. The CDC has reported that infection with HIV is the major factor for transforming latent TB infection into an active disease [8].…”
Section: Introductionmentioning
confidence: 99%